Fenomena Pariwisata Halal di Kota Batu - Safitri, Sri Wahyuni (ITB AAS INDONESIA Surakarta, 2024)
In recent decades, halal tourism has started to gain a lot of interest, it is considered a strategic way for the future of tourism. Tourist destinations can be said to be halal tourism if Muslim tourists have their main needs met. The meaning of halal tourism is viewed in different directions between the government and business actors. With the meaning of halal tourism, is it possible that it is only limited to branding and improving the nation's image for commercial purposes or is it dominated by economic interests as a business opportunity, even though halal tourism is not only limited to physical pleasure but Islamic values are also realized so that spiritually it is also fulfilled. Study. using qualitative research. This research uses a phenomenological approach. This approach is used to understand how business actors and tourists interpret and explore halal tourism in Batu City according to its concepts and practices. This research uses primary data sources and secondary data. Researchers collected primary data through in-depth interviews and direct observation with tourists visiting the Batu City tourist destination.